Influence of user-generated content on tourist visit intention: a literatur review - Madaniah, Sarah; Situmorang, Syafrizal Helmis; Sembiring, Beby Karina Fawzee (Jurnal Mantik, 2024)
This research aims to examine how user-generated content (UGC) affects travelers' intent to visit, as well as how UGC affects travel choices and offers suggestions for efficient tourism marketing tactics. A systematic literature review (SLR) was conducted across two reputable databases, ScienceDirect and Scopus, using specific keywords to locate relevant studies. 485 of the 556 articles were deemed relevant when the inclusion and exclusion criteria were applied. These papers were then thoroughly reviewed to generate a comprehensive study of the topic. The selection process, which included evaluating the titles and abstracts of every article located, produced a careful selection of 71 publications for full-text analysis. Ultimately, 26 papers were chosen for further analysis in this study. The findings from recent studies underscore the significant impact of user-generated content (UGC) on shaping tourists' intentions to visit destinations. This research shows that user-generated content (UGC) emotionally influences tourists' travel intentions, which is crucial for developing more effective and credible tourism marketing strategies